PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN DI LINGKUNGAN SEKOLAH PADA MATERI KEANEKARAGAMAN HAYATI DI KELAS X-MIA MAS AR-ROSYIDIYAH - Garnasih, Tuti (Jurnal BIOEDUIN, 2018)
The analysis result of student daily examination on biology study is still below the Minimum Criterion of Completeness (KKM).It indicate low motivation of students' learning on biology subject, due to the dominant application of teacher-centered learning. The purpose of this study was to improve motivation and learning outcomes of Biology X-MIA students in MAS Ar-Rosyidiyah Cibiru Bandung, on 2017/2018 school year. The subjects of this study were X-MIA class students as much as 34 students, on biodiversity topic.The results showed that the application of learning outside the classroom in the school zone can increase motivation and learning outcomes of X-MIA students on biology. Student learning motivation in cycle I was 72,24% increased by 85,50% in cycle II. The result of cognitive domain in cycle I was 82,35% to 88,23% in cycle II, whereas learning result of student affective aspect in cycle I was increasing from 82,29% to 85,15% in cycle II.